Pattern of Neuropsychiatric Illness in Children and Adolescent Presented in Psychiatry OPD of a Tertiary Care Hospital in North Lakhimpur District of Assam - Baruah, Kristi; Kalita, Bitupan; Bhattacharjee, Pallab Kumar (National Journal of Medical Research, 2025)
Background: Understanding the neuropsychiatric morbidity among the children and adolescent is very essential for the promotion of mental and physical well- being. By looking into the patterns, magnitude of various neuropsychiatric illness among children and adolescents’ effective preventive and control strategies can be formulated. Considering all these perspectives the present study has been undertaken with the objective to assess the pattern of neuropsychiatric illness and also to assess the age, sex, religion, caste and locality of the in children and adolescents presented to psychiatry OPD of a tertiary care hospital in North Lakhimpur, Assam. Methodology: This was a retrospective cross-sectional study conducted in Lakhimpur Medical College and Hospital, Assam, India. Data were collected from case record of all children of age group 2-19 years who attended psychiatry OPD at Lakhimpur Medical College from October 2022 to September 2023. Results: A total of 241 patients of age group 2-19 years were found, out of which 46 patients were excluded because incomplete data. 92.3% of the patients had one neuropsychiatric illness and 7.7% had more than one diagnosis. Among all neuropsychiatric illness, mental retardation was present in majority 24.62% of children and adolescents followed by dissociative disorders (15.38%) and anxiety disorders (10.26%) respectively. Conclusions: To conclude, mental retardation and dissociative disorder have remained the predominant diagnosis in the present study with 92.3% of patients with single illness and 7.7% with co morbidities.